English for academic and professional purposes - Go, Ronald S. (Makati City : Diwa Learning Systems, Inc., 2019)
"This book offers practical lessons and engaging activities that allow you to read, write, and interact with people. It contains modules organized into two units based on the content requirements of the K to 12 curriculum of the Department of Education. The first unit will teach you how to use techniques and strategies to further enhance your reading and critical thinking skills. The second unit will provide you with opportunities to produce texts that are technical in nature."
Includes bibliography.
English text.
Keywords: English language - Composition and exercises; Reading comprehension - Problems, exercises, etc